The survey and representation for the safeguard of the cultural heritage in case of emergency: A Case Study on Safeguarding Cultural Heritage and Utilizing Modern Survey Techniques (Journal of Advances and Scholarly Researches in Allied Education, 2022)
In this short article we aim to describe the strategy and technique used to survey the Churchof Sant'Andrea in Campi di Norcia, which was severely damaged by the 2016 earthquake. The churchstands at the entrance of the village, in a position of relevant importance for the landscape of the ValCastoriana, on which the village overlooks. Therefore, considering the framework of damage suffered bythe building and its position with respect to the access system of the village, the main objective was tosecure the space surrounding the building, aiming to counteract movements of the decks andstrengthen the damaged elements, to prevent further collapses. After the securing of the building, it waspossible to proceed with the survey campaign. We describe the difficulties encountered due to thepresence of rubble and the elements to secure the building, stressing that the survey of cultural heritage,especially in the field of property destroyed by the earthquake, is one of the most representativescenarios in which to use and test modern detection techniques. In fact, recent digital technologies offerthe possibility of obtaining new products not only from the survey activities but also in the fields ofrepresentation and visualization, with the aim of having an accurate description of the territory, citiesand buildings.